2015
DOI: 10.1177/0143034315612144
|View full text |Cite
|
Sign up to set email alerts
|

Examining the context of instruction to facilitate student success

Abstract: Identifying effective instructional practices and effective teachers is an important issue in educational research, policy, and practice. However, many schools have resorted to measuring these constructs with student test scores, ignoring the instructional context. In this introductory article to the special issue, we highlight the importance of the instructional context as facilitating of teacher-student relationships, effective instructional practices, and supporting of student success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Gender differences in TA were reported as a robust finding, with female students experiencing higher levels of test anxiety than male students (r = .21; von der Embse et al, 2018). This disparity between genders occurs at all grade levels and is a gap that seems to increase during primary and secondary school years, and then slightly decrease in post-secondary education (von der Embse et al, 2018). Although several studies suggested that gender differences are predominantly (or solely) attributable to increased emotionality in females (e.g.…”
Section: Test Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Gender differences in TA were reported as a robust finding, with female students experiencing higher levels of test anxiety than male students (r = .21; von der Embse et al, 2018). This disparity between genders occurs at all grade levels and is a gap that seems to increase during primary and secondary school years, and then slightly decrease in post-secondary education (von der Embse et al, 2018). Although several studies suggested that gender differences are predominantly (or solely) attributable to increased emotionality in females (e.g.…”
Section: Test Anxietymentioning
confidence: 99%
“…verbal, visuospatial components, short-term and WM tasks) into four complexity levels. Furthermore, in contrast to von der Embse et al (2018), who investigated the influence of TA on a range of educational outcomes, we only included studies that directly tested the specific relationship between TA and math performance. Lastly, we also extended the level of analysis by looking at the mediating role of WM to shed further light on its specific weight within the MA-math achievement relationship.…”
Section: The Current Meta-analysismentioning
confidence: 99%
“…In the era of performance-based educational accountability policies, schools are particularly keen to identify areas that may contribute to academic underperformance on high-stakes examinations (von der Embse & Putwain, 2015). Within school settings, there has been an increased focus on “academic anxieties” (Cassady, 2010) which is a class of anxieties that is both context and content specific.…”
Section: Current Studymentioning
confidence: 99%
“…While there is a clear need to assess and reduce teacher stress, Renshaw, Long, and Cook (2015) have suggested that measures focusing solely on the negative aspects of teacher psychological functioning fail to capture the entirety of the construct. As such, it is essential to understand the psychological factors that are positively associated with effective teaching (von der Embse & Putwain, 2015). Van Horn, Taris, Schaufeli, and Schreurs (2004) have developed a model of occupational well-being that emphasizes teachers’ healthy and successful functioning at work.…”
Section: Introductionmentioning
confidence: 99%